Improving depression-like behaviors caused by diabetes is likely to offer a new perspective for the treatment of non-healing chronic wounds - Dong, Zhiqin; Wu, Jijin; Cao, Hanchen; Lu, Jinqiang (Frontiers in Behavioral Neuroscience, 2024)
Background Three phases are often involved in the intricate process of wound healing: inflammatory exudation, cell proliferation, and tissue remodeling. It is challenging for wounds to heal if conditions like ischemia, persistent pressure, infection, repetitive trauma, or systemic or localized illnesses arise during the healing process. Chronic wounds are persistent injuries that do not follow the normal healing process and fail to progress through the stages of healing within a reasonable timeframe, like diabetic ulcers, vascular ulcers, pressure sores, and infectious wounds. Various factors affect chronic wound healing. A large body of research has illuminated that psychological distress may often be related to wound healing in clinical settings. Our observations have indicated that the pace of wound healing in diabetic mice is generally slower than that of healthy mice, and mice induced by streptozotocin (STZ) and fed a high-fat diet generally exhibit depression-like behavior. Our experiment delves into whether there is an inherent correlation and provides new ideas for clinical treatment to promote wound healing. Methods In order to explore the relationship between diabetes, depression, and wound healing, we observed wound healing through HE staining, Masson's trichrome staining, and IHC staining for CD31 and detected the depressive condition through behavioral tests. Then, RT-PCR was used to detect the mRNA expression levels of α-SMA, Col1, CD31, and VEGF in wound tissue. Finally, the related brain areas were regulated through chemical genetic methods and the process of wound healing was observed. Conclusion It has been observed that the lateral habenula (LHb) areas are associated with depression-like behavior induced by diabetes. Inhibiting LHb neuronal activity mitigates these depressive symptoms and enhances wound healing. Refractory wounds can be improved by considering patients' emotional issues from a broad standpoint, which provides fresh concepts for potential clinical treatments in the future.